Nowe dane o występowaniu bogatkowatych (Coleoptera: Buprestidae) na terenie Puszczy Białowieskiej - Gutowski, Jerzy; Królik, Roman; Sućko, Krzysztof; Sweeney, Jon; Ługowoj, Jerzy (Leśne Prace Badawcze, 2019)
The aim of this work was to expand current knowledge on the species composition and distribution of the jewel beetles (Coleoptera: Buprestidae) in the Białowieża Primeval Forest (BPF) based on research conducted in the years 2000–2018 and a literature review. The BPF is considered the best-preserved forest of the European lowland and is a reference point for all forest research. Thus, knowledge of its fauna is vital. This research was conducted and incorporated the whole Polish part of the BPF, including Białowieża National Park (BNP), using standard methods for faunistic studies of terrestrial beetles. We also investigated potential microhabitats of saproxylic buprestid beetles and reared larvae from inhabited host material. Collected larvae and/or pupae were identified in the laboratory or grown to the adult stage. However, most specimens were collected using various traps (Lindgren, Moericke, barrier type Netocia and IBL-2), especially traps placed in the upper tree canopy.Two species previously unrecorded in the BPF (Agrilus graminis, A. mendax) and new information on several of the rarest Central European Buprestidae species (Buprestis splendens, Eurythyrea quercus, Anthaxia chevrieri, Chrysobothris chrysostigma, Agrilus antiquus croaticus, A. ater, A auricollis, A. convexicollis, A. pseudocyaneus) are presented here. Currently, 54 species of Buprestidae are known to occur the BPF area, of which 49 were collected from the Polish part and 26 were collected from the Belarusian part, whilst two species (Dicerca berolinensis and Eurythyrea austriaca) have no specific location data. In the BNP, which covers about 17% of the Polish part of the BPF, up to 39 species of buprestid beetles have been found. We also provide an original key for differentiating Agrilus nicolanus – a species recently discovered in Poland (BPF and Biebrza Valley), that was previously known to occur only in Asia and the Lipetsk region in the European part of Russia – from Agrilus betuleti species group. In conclusion, the BPF is an important refugium of buprestid beetle richness including known forest relics.